Strumal carcinoid of the ovary - a case report - Asani, Learta; Zdravkovski, Panche; Kostadinova Kunovska, Slavica (Macedonian Association of Pathology, 2016)
Objective: Primary ovarian carcinoids comprise 0.1% of all ovarian malignancies and approximately 0.5-1.7% of all carcinoid tumors. Strumal carcinoid (SC) is a type of germ cell tumor characterised by an intimate mixture of thyroid tissue and carcinoid with other teratomatous elements. Material and Methods: A 47-years-old woman was referred to gynecology department with complex bilateral adnexal masses for surgery. On gross examination, the right ovary was 11x10x7 cm, yellowish brown in color, with a polynodular surface, and the left ovary was 8x7.5x7 cm with a smooth surface. Cut sections revealed predominantly cystic multilocular masses, partially filled with greasy content with hair and smooth solid areas. Results: On histopathologic examination the cystic spaces of the right ovary were lined by squamous epithelium with underlying adnexal structures, glandular epithelium and thyroid follicles containing colloid. All tissue components were mature. Among the thyroid follicles there was a population of monomorphic cells with moderate amount of eosinophilic cytoplasm, arranged in solid, trabecular and rosetoid patterns suggestive of a carcinoid. The suspicion has been confirmed by the immunoprofile of the tumor cells, which were diffusely immunopositive for CKAE1/AE3, synaptophysin, chromogranin, NSE and CD57, and the thyroid follicles including the central colloid were immunopositive for thyroglobulin, TTF-1 and thyroid peroxidase (TPO). The left ovarian cyst was a dermoid cyst. Conclusions: The differential diagnosis of SC includes other entities, such as granulosa-cell tumor and Sertoli-Leydig-cell tumor. However, characteristic histological pattern, immunoprofile, and in some cases the clinical manifestations due to the neuroendocrine activity of the tumor, are usually conclusive for the diagnosis.
Keywords: ovarian; carcinoid; strumal; germ cell